Technological Challenges of Autoclave Design for Ammonothermal Syntheses - Schlücker, Eberhard; Kimmel, Anna-Carina (Ammonothermal Synthesis and Crystal Growth of Nitrides, 2021)
The challenges of ammonothermal reactor design are manifold. High-pressure and temperature require the use of high-performance alloys with sufficient strength at elevated temperature and excellent creep resistance: highly alloyed Ni-base and Co-base alloys and a Mo-base alloy have been in use in ammonothermal reactor design. Furthermore, the dimensioning rules have to be strictly followed to minimize stress concentration. Repeated loading cycles and degradation over time have to be considered. Finally yet importantly, good handling of the equipment not only minimizes the workload but also reduces the risk of crucial operating errors. The chapter Technological challenges of autoclave design discusses design options for high-pressure at high-temperature equipment with regard to their mechanic and thermal stability. Materials suitable for ammonothermal pressure vessels will be reviewed and some basic safety advice is given at the end of this chapter.
CRIS-Team Scopus Importer:2021-03-05